Nowożytne innowacje w postrzeganiu i przedstawianiu religii - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2016)
In the pages that follow I recall examples of those innovations in perceiving and representing diverse religions and forms of religiosity that had occurred in the Enlightenment period and the times that followed after. What makes a common denominator is an attempt to leave the confessional point of view and move towards post-confessional and scientific view. It is questionable if in every of the recalled examples it had such a character. I do hope, however, that at least the examples do show some ways and approaches in treating modern studies of religion as a scientific discipline.
Keywords: oświeceniowe innowacje; Weberowskie innowacje